Bivalirudin, a bivalent, thrombin specific anticoagulant as an alternative to heparin in interventional procedures - Chew, D. P. (Hämostaseologie, 2002)
Among the antithrombotic therapies evaluated to date, the synthetic peptide bivalirudin is unique in its ability to reduce both ischemic and bleeding complications associated with percutaneous coronary intervention (PCI). Bivalirudin is a small peptide consisting of 20 amino acid residues that binds thrombin in a direct, reversible, and bivalent fashion. The agent is approved for use in the United States and New Zealand as an anticoagulant in patients with unstable angina undergoing PCI and may also prove beneficial in patients with acute coronary syndromes (ACS), acute myocardial infarction (AMI) and in patients undergoing coronary artery bypass graft (CABG) procedures. This article examines bivalirudin in more detail.
Keywords: Bivalirudin; anticoagulant; percutaneous coronary intervention; thrombin inhibitor; unstable angina